2016
DOI: 10.9734/ijtdh/2016/27369
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Prevalence of Onchocerca volvulus Infection among the Inhabitants of Awgu and Oji-River Local Government Areas of Enugu State, Nigeria

Abstract: This study was conducted to determine the prevalence of Onchocerciasis among the inhabitants of Awgu and Oji River Local Government Areas from October 2012 to March 2013. Simple random sampling method was used to select three communities in each Local Government Area. The prevalence of O. volvulus infection was determined by microscopic examination of skin snip samples for O. volvulus microfilaria. The subjects were selected from the communities by systematic random sampling method. Seven hundred and eighty si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
0
4
Order By: Relevance
“…In addition, because of their outdoor activities, these individuals are usually absent during household-based direct observance mass administration of ivermectin and this might therefore explain why these groups exhibit a low adherence to ivermectin treatment. Our observations disagree with the findings of Ikpo et al [28] who reported a peak prevalence of onchocerciasis among individuals aged 41-50 years-old in the Oji River Local Government Area (Enugu State, Nigeria). In fact, onchocerciasis is known to be naturally cumulative, but treatments administered for 18-21 years might have disrupted this relationship, thus favoring the shift in prevalence peak among individuals highly exposed and poorly compliant with ivermectin mass treatments.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, because of their outdoor activities, these individuals are usually absent during household-based direct observance mass administration of ivermectin and this might therefore explain why these groups exhibit a low adherence to ivermectin treatment. Our observations disagree with the findings of Ikpo et al [28] who reported a peak prevalence of onchocerciasis among individuals aged 41-50 years-old in the Oji River Local Government Area (Enugu State, Nigeria). In fact, onchocerciasis is known to be naturally cumulative, but treatments administered for 18-21 years might have disrupted this relationship, thus favoring the shift in prevalence peak among individuals highly exposed and poorly compliant with ivermectin mass treatments.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, individuals whose age was 45 years and above were nearly ten times more likely to develop the infection as compared to individuals in the age group of 15-24 years. The finding was in agreement with findings of studies conducted in Jimma zone, West Welega zone, Nigeria, Equatorial Guinea, and Senegal where age was independently associated with onchocerciasis infection [9,13,[15][16][17][18]. This might be due to the fact that adults are most of the time engaged in outdoor activities where they can be bitten by black fly.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, because of their outdoor activities, these individuals are usually absent during household-based direct observance mass administration of ivermectin and this might therefore explain why these groups exhibit a low adherence to ivermectin treatment. Our observations disagree with the ndings of Ikpo et al [28] who reported a peak prevalence of onchocerciasis among individuals aged 41-50 years-old in the Oji River Local Government Area (Enugu State, Nigeria). In fact, onchocerciasis is known to be naturally cumulative, but treatments administered for 18-21 years might have disrupted this relationship, thus favoring the shift in prevalence peak among individuals highly exposed and poorly compliant with ivermectin mass treatments.…”
Section: Discussioncontrasting
confidence: 99%